Optical fiber preform quartz rod welding thermal protection coating

By using spherical high-purity alumina composite powder and UHTC coating during the welding process of fiber prefabricated rods, combined with graphene nanosheets and white corundum sandblasting technology, the problem of heat deformation of the quartz rod hanging head is solved, achieving high precision and the high-efficiency welding process significantly improves the hardness and corrosion resistance of the coating.

CN119176669APending Publication Date: 2024-12-24DEQING CHUANGZHI TECH CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411396877.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-09
Publication Date
2024-12-24

AI Technical Summary

Technical Problem

During the melting and shrinking of the optical fiber prefabricated rod, the heat deformation of the quartz rod hanging head leads to a reduced position accuracy and production efficiency, and it is easy to waste materials.

Method used

Using spherical high-purity alumina composite powder and UHTC high-temperature corrosion-resistant coating, high-purity alumina is prepared by ultrasonic assistance, and combined with graphene nanosheets and white corundum sandblasting to form a wear-resistant and anti-corrosion coating, using plasma Spraying technology sprays at the hanging head position to improve bond strength and thermal deformation resistance.

Benefits of technology

Effectively prevent thermal deformation of the quartz rod hanging rod head, ensure position accuracy, improve production efficiency, and significantly reduce material waste. The high hardness and corrosion resistance of the coating are significantly improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119176669A_ABST
    Figure CN119176669A_ABST
Patent Text Reader

Abstract

The invention relates to a thermal protection coating for fusion welding of a quartz rod of an optical fiber preform. The thermal protection coating comprises the following steps: preparing a spherical high-purity aluminum oxide raw material, preparing spherical high-purity aluminum oxide composite powder, preparing a UHTC high-temperature-corrosion-resistant coating raw material composition, and pre-treating a hanging head and performing plasma spraying. The thermal protection coating is subjected to plasma spraying on the hanging rod head of a quartz handle rod of an optical fiber preform, a multi-layer structure of composite powder of spherical high-purity aluminum oxide and graphene nanosheets and a high-temperature-corrosion-resistant coating is added into the thermal protection coating, and the porosity of the obtained aluminum oxide protection coating at the hanging head position is detected to be 4-6%; the microhardness reaches HV800-1000, the coating is high in strength and resistant to high temperature, a quartz base material is protected against deformation, and the working state is effective and stable.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of thermal protection, and in particular to a thermal protection coating for welding a quartz handle bar of an optical fiber preform rod. Background Art

[0002] Communication optical fiber is drawn from optical fiber preform rods. The optical fiber preform rods are made by CVD process, which deposits gaseous halides and oxygen at 1000℃ in a high-purity quartz glass tube, and then uses a high-temperature hydrogen-oxygen flame to melt the tube into a solid preform rod.

[0003] However, during the manufacturing process, when the preform rod melts and shrinks, one end of the preform rod needs to be welded to the quartz handle rod first. During welding, the flame of the spray gun is transmitted to the quartz rod, generating a high temperature of about 1200°C. The hanging head position of the handle rod is deformed by the heat, affecting the accuracy of the hanging position.

[0004] The thermal deformation of the hanging rod head not only affects the positioning accuracy, but also reduces production efficiency and wastes materials. Summary of the invention

[0005] The technical purpose of the present invention is to solve the problems in the background technology and provide a thermal protection coating for welding quartz handle bars of optical fiber preform rods.

[0006] The above technical objectives of the present invention are achieved through the following technical solutions: A thermal protection coating for a quartz handle of an optical fiber preform rod is fused, and the fusion thermal protection coating comprises the following preparation steps: Step S1: Preparation of spherical high-purity alumina raw material: The spherical high-purity alumina is obtained by ultrasonicating aluminum powder in ultrapure water; Step S2: preparing spherical high-purity alumina composite powder: mixing the high-purity alumina prepared in step S1 with a trace amount of graphene nanosheets to prepare the spherical high-purity alumina composite powder; Step S3: Preparation of raw material composition of UHTC high temperature corrosion resistant coating: the raw materials for preparing the UHTC high temperature corrosion resistant coating include aluminum oxide, inert powder, metal oxide and auxiliary powder; Step S4: Pre-treatment of the hanging head: Affix protective tape to the end surface of the quartz handle bar and other non-coated areas of the handle bar, and then sandblast the hanging head for roughening; Step S5 plasma spraying: spray the high-purity alumina composite powder and UHTC high-temperature corrosion-resistant coating prepared in step S2 and step S3 at the hanging head position in sequence, so as to obtain a thermal protection coating for the fusion welding of the optical fiber preform quartz handle.

[0007] Preferably, the raw material for preparing the spherical high-purity alumina raw material in step S1 further includes tetramethylammonium hydroxide, and the preparation process is: mixing tetramethylammonium hydroxide with pure water, wherein the resistivity of the pure water is greater than 10 5Ω·cm, and then aluminum powder is added, wherein the Al content of the aluminum powder is greater than 99.999%, and the above solution is reacted at 80-90°C and 35-45kHz ultrasonic frequency for 2h to obtain a slurry; the slurry is filtered, dried at 40-60°C and calcined at 1200-1300°C to obtain the high-purity alumina powder.

[0008] The advantage of adopting the present invention is that the high-purity aluminum oxide in the coating of the present invention is prepared in pure water by ultrasound assistance and the addition of tetramethylammonium hydroxide. The spherical ultrafine high-purity aluminum oxide prepared by this method can use ultrasound to destroy the gas barrier film at the initial stage of the reaction, thereby increasing the reaction potential energy of the aluminum surface, accelerating the reaction rate, and improving the dissociation rate of the corresponding crystal face crystals. Not only can high-purity spherical aluminum oxide with a purity of more than 99.999% and extremely few impurities be obtained, but the obtained aluminum oxide particle size is less than 350nm, and its fine particle size is of great benefit to the preparation of the coating in the present invention.

[0009] Preferably, the mass fraction of the graphene nanosheets in step S2 is 0.1-0.5 parts; the mass fraction of high-purity alumina is 99.5-99.9 parts; the preparation process of the spherical high-purity alumina composite powder is as follows: the graphene nanosheets and high-purity spherical alumina powder are evenly mixed according to the ratio and ball-milled for 3-8 hours, the ball-milled mixed powder is dried at 50-80°C, and then a polyvinyl alcohol solution is added for granulation, and the mass ratio of the mixed powder of graphene nanosheets and high-purity spherical alumina to the polyvinyl alcohol solution is (1-5):1.

[0010] Preferably, the graphene nanosheet is composed of a plurality of stacked graphene layers, the graphene nanosheet has 6-8 layers, a total thickness of 1.8-2.5 nm, and a size of 3-5 μm.

[0011] The advantage of adopting the present invention is that the present invention uses graphene nanosheets and nano-alumina as a composite, and under the spraying parameters, the bonding strength between the alumina ceramic coating and the substrate is increased. The composite of a small amount of graphene nanosheets greatly enhances the wear resistance and corrosion resistance of the nano-alumina ceramic coating, making the present invention more economical.

[0012] The present invention has the advantage that adding graphene nanosheets to the plasma sprayed aluminum oxide coating can improve the tribological properties: graphene has high fracture toughness and excellent lubricity, and can be used to enhance the tribological properties of the coating system for resisting wear.

[0013] Preferably, in step S3, the inert powder is zirconium dioxide ZrO2 or mullite powder; the metal oxide is a combination of calcium oxide, magnesium oxide and zinc oxide; and the auxiliary agent powder is silicon dioxide or boron trioxide.

[0014] Preferably, the preparation process of the UHTC high temperature corrosion resistant coating raw material composition is to uniformly mix the above-mentioned inert powder, metal oxide and auxiliary powder in proportion, and then put them into a ball mill in a dry state and liquid phase sinter them, and the sintering temperature is 1300-1400°C; the sintered powder is taken out and ball milled for a second time, and finally dried at 80-100°C to obtain the UHTC high temperature corrosion resistant coating raw material composition powder; wherein the mass fraction of the inert powder is 1-5 parts, the mass fraction of the metal oxide is 1-5 parts, the mass fraction of the auxiliary powder is 0.5-2 parts, and the rest is high purity alumina powder; in the inert powder, the mass ratio of zirconium dioxide ZrO2 and mullite powder is 3:1; in the metal oxide, the mass ratio of calcium oxide, magnesium oxide and zinc oxide is (1-2):1:1.

[0015] The advantage of adopting the present invention is that the relatively high porosity of the plasma sprayed ultra-high temperature ceramic (UHTC) coating has always been an important limiting factor for the ablation performance, and the ceramic coating has great potential in protecting pipes from high temperature corrosion; the preparation of the UHTC coating added in the present invention can play a good role in corrosion resistance, tensile strength, bending resistance and thermal deformation resistance, which is of great significance for optical fiber preform rods.

[0016] Preferably, in the hanging head pretreatment of step S4, 80#-120# white corundum sand is used for sandblasting, the sandblasting pressure is 0.15-0.3Mpa, the sandblasting angle is 70°-80°, the coating position is coarsened uniformly and finely, and the surface roughness reaches Ra: 2.0-2.5um.

[0017] The invention has the advantages that white corundum is made of high-quality aluminum oxide powder as raw material, and white corundum is crystallized by electric melting, high purity, good self-sharpening, acid and alkali corrosion resistance, high temperature resistance, and stable thermal performance. White corundum has a slightly higher hardness than brown corundum, and slightly lower toughness, but has high purity, good self-sharpening, strong grinding ability, low heat generation, high efficiency, acid and alkali corrosion resistance, and good high temperature thermal stability. Abrasives made of white corundum granular sand are suitable for grinding fine-grained abrasives such as high-carbon steel, high-speed steel and stainless steel. Sandblasting white corundum is a widely used abrasive with dense texture, high hardness, and sharp-angled grains. It is suitable for manufacturing ceramics, resin-bonded abrasives, grinding, polishing, sandblasting, precision casting, etc. It can also be used to manufacture advanced refractory materials; white corundum sandblasting can make the surface of an object obtain a certain degree of cleanliness and roughness, thereby increasing the adhesion of the surface of the object, so that the coating and the surface of the object are more closely combined and not easy to fall off, greatly increasing the service life of the surface coating.

[0018] Preferably, in the plasma spraying step S5, the UHTC high temperature corrosion resistant coating is sprayed first, and then the spherical high purity alumina composite powder is sprayed, and the spraying thickness ratio of the UHTC high temperature corrosion resistant coating / spherical high purity alumina composite powder is 1:(8.8-10.5).

[0019] The invention has the advantages of first plasma spraying UHTC and then spraying the spherical high-purity alumina composite coating, which can improve the conventional mechanical properties of the pipe fittings and also enhance their corrosion resistance and thermal deformation resistance.

[0020] The present invention has the advantages that the UHTC coating is thinner and the spherical high-purity alumina composite coating is thicker, because the UHTC used in the present invention can achieve better effects with only a small amount, which saves production costs while achieving greater benefits.

[0021] The present invention has the advantage that the optical fiber preform quartz handle welding thermal protective coating of the present invention can be applied to the process of welding the optical fiber preform to the quartz handle, and the obtained alumina protective coating at the hanging head position has a porosity of 4-6%, a microhardness of HV800-1000, high coating strength, high temperature resistance, and can protect the quartz substrate from deformation, and the working state is effective and stable.

[0022] In summary, the present invention has the following beneficial effects: 1. By optimizing the spherical production process of high-purity alumina in the pre-production process and utilizing the ultrasound-assisted tetramethylammonium hydroxide preparation process, the spherical ultrafine high-purity alumina prepared by this method can destroy the gas barrier film at the initial stage of the reaction, thereby increasing the reaction potential energy of the aluminum surface, accelerating the reaction rate, and improving the dissociation rate of the corresponding crystal face crystals. Not only can high-purity spherical alumina with a purity of more than 99.999% and extremely few impurities be obtained, but also the obtained alumina particle size is less than 350nm, and its fine particle size is of great benefit to the preparation of the coating in the present invention; 2. By compounding spherical high-purity alumina with trace graphene nanosheets, the bonding strength between the alumina ceramic coating and the substrate can be increased. Compounding a small amount of graphene nanosheets can also enhance the wear resistance and corrosion resistance of the nano alumina ceramic coating; 3. By adding UHTC raw material technology to the coating, it can play a good role in corrosion resistance, tensile strength, bending resistance and thermal deformation resistance, which is of great significance for optical fiber preform; 4. The coating process of the present invention combines white corundum sandblasting and plasma spraying, and is applied to the thermal protection coating of the quartz handle bar fusion of the optical fiber preform rod. It can effectively prevent the thermal deformation of the quartz handle bar hanging rod head during the dissolution of the optical fiber preform rod, and has other excellent properties to ensure the shape accuracy of the position. The high hardness of the coating can effectively resist the force during hanging and protect the substrate from damage. BRIEF DESCRIPTION OF THE DRAWINGS

[0023] Figure 1 It is a schematic diagram of the process of fusing the thermal protection coating of the optical fiber preform quartz rod in the present invention. DETAILED DESCRIPTION

[0024] The following specific embodiments are merely explanations of the present invention and are not limitations of the present invention. After reading this specification, those skilled in the art may make modifications to the embodiments without any creative contribution as needed. However, such modifications are protected by the patent law as long as they are within the scope of the claims of the present invention. Example 1

[0025] like Figure 1 As shown, step S1 is to prepare a spherical high-purity alumina raw material: the spherical high-purity alumina is obtained by ultrasonically preparing aluminum powder in ultrapure water: tetramethylammonium hydroxide is mixed with pure water, wherein the resistivity of the pure water is greater than 10 5 Ω·cm, and then aluminum powder is added, wherein the Al content of the aluminum powder is greater than 99.999%, and the above solution is reacted at 80°C and 35kHz ultrasonic frequency for 2h to obtain a slurry; the slurry is filtered, dried at 40°C and calcined at 1200°C to obtain the high-purity alumina powder.

[0026] Step S2 prepares spherical high-purity alumina composite powder: the high-purity alumina prepared in step S1 is mixed with a trace amount of graphene nanosheets to obtain the spherical high-purity alumina composite powder; the mass fraction of the graphene nanosheets is 0.5 parts, and the graphene nanosheets are composed of multiple stacked graphene layers, the graphene nanosheets are 6 layers, the total thickness is 1.8nm, and the graphene nanosheet size is 3μm; the mass fraction of high-purity alumina is 99.5 parts; the preparation process of the spherical high-purity alumina composite powder is as follows: the graphene nanosheets and high-purity spherical alumina powder are evenly mixed according to the ratio and ball-milled for 3h, the ball-milled mixed powder is dried at 50°C, and then a polyvinyl alcohol solution is added for granulation, and the mass ratio of the mixed powder of graphene nanosheets and high-purity spherical alumina to the polyvinyl alcohol solution is 1:1.

[0027] Step S3 Preparation of UHTC high temperature corrosion resistant coating raw material composition: The raw materials for preparing the UHTC high temperature corrosion resistant coating include alumina, inert powder, metal oxide and auxiliary powder; the preparation process of the UHTC high temperature corrosion resistant coating raw material composition is to mix the above-mentioned inert powder, metal oxide and auxiliary powder in proportion, and then put them into a ball mill in a dry state and then liquid phase sinter them, and the sintering temperature is 1300°C; the sintered powder is taken out and ball milled for a second time, and finally dried at 80°C to obtain the UHTC high temperature corrosion resistant coating raw material composition powder; wherein the mass fraction of the inert powder is 1 part, the mass fraction of the metal oxide is 1 part, the mass fraction of the auxiliary powder is 0.5 part, and the rest is high-purity alumina powder; in the inert powder, the mass ratio of zirconium dioxide ZrO2 and mullite powder is 3:1; in the metal oxide, the mass ratio of calcium oxide, magnesium oxide and zinc oxide is 1:1:1.

[0028] Step S4: Pretreatment of the hanging head: A protective tape is attached to the end face of the quartz handle bar and other non-coated areas of the handle bar, and then the hanging head is sandblasted for roughening; 80#-120# white corundum sand is used for roughening, the sandblasting pressure is 0.15Mpa, the sandblasting angle is 70°, the coating position is roughened evenly and finely, and the surface roughness reaches Ra: 2.0um; the UHTC high temperature corrosion resistant coating / spherical high purity alumina composite powder spraying thickness ratio is 1:8.8.

[0029] Step S5 plasma spraying: spray the high-purity alumina composite powder and UHTC high-temperature corrosion-resistant coating prepared in step S2 and step S3 at the hanging head position in sequence, use spray granulated spherical high-purity alumina powder as the coating material, the powder has high sphericity and good fluidity, the powder particle size distribution range is 15-45μm, the alumina purity is above 99.5%, use plasma spraying process, spraying current 600A, voltage 75V, main gas is argon, flow rate 45L / M, secondary gas is hydrogen, flow rate 7.5L / M, powder feeding rate 25g / min, coating thickness 0.05mm, that is, a thermal protective coating for optical fiber preform quartz handle fusion is obtained. Example 2

[0030] Step S1: Preparation of spherical high-purity alumina raw material: The spherical high-purity alumina is obtained by ultrasonication of aluminum powder in ultrapure water: Tetramethylammonium hydroxide is mixed with pure water, wherein the resistivity of the pure water is greater than 10 5 Ω·cm, and then aluminum powder is added, wherein the Al content of the aluminum powder is greater than 99.999%, and the above solution is reacted at 90°C and 45kHz ultrasonic frequency for 2h to obtain a slurry; the slurry is filtered, dried at 60°C and calcined at 1300°C to obtain the high-purity alumina powder.

[0031] Step S2 prepares spherical high-purity alumina composite powder: the high-purity alumina prepared in step S1 is mixed with a trace amount of graphene nanosheets to obtain the spherical high-purity alumina composite powder; the mass fraction of the graphene nanosheets is 0.1 parts, and the graphene nanosheets are composed of multiple stacked graphene layers, the graphene nanosheets are 8 layers, the total thickness is 2.5nm, and the graphene nanosheet size is 5μm; the mass fraction of high-purity alumina is 99.9 parts; the preparation process of the spherical high-purity alumina composite powder is as follows: the graphene nanosheets and high-purity spherical alumina powder are evenly mixed according to the ratio and then ball-milled for 8h, the ball-milled mixed powder is dried at 50-80℃, and then a polyvinyl alcohol solution is added to granulate, and the mass ratio of the mixed powder of graphene nanosheets and high-purity spherical alumina to the polyvinyl alcohol solution is 5:1.

[0032] Step S3 Preparation of UHTC high temperature corrosion resistant coating raw material composition: The raw materials for preparing the UHTC high temperature corrosion resistant coating include alumina, inert powder, metal oxide and auxiliary powder; the preparation process of the UHTC high temperature corrosion resistant coating raw material composition is to mix the above-mentioned inert powder, metal oxide and auxiliary powder in proportion, and then put them into a ball mill in a dry state and then liquid phase sinter them at a sintering temperature of 1400°C; take out the sintered powder and ball mill it for a second time, and finally dry it at 100°C to obtain the UHTC high temperature corrosion resistant coating raw material composition powder; wherein the mass fraction of the inert powder is 5 parts, the mass fraction of the metal oxide is 5 parts, the mass fraction of the auxiliary powder is 2 parts, and the rest is high-purity alumina powder; in the inert powder, the mass ratio of zirconium dioxide ZrO2 and mullite powder is 3:1; in the metal oxide, the mass ratio of calcium oxide, magnesium oxide and zinc oxide is 2:1:1.

[0033] Step S4: Pretreatment of the hanging head: A protective tape is attached to the end face of the quartz handle bar and other non-coated areas of the handle bar, and then the hanging head is sandblasted for roughening; 80#-120# white corundum sand is used for roughening, the sandblasting pressure is 0.3Mpa, the sandblasting angle is 80°, the coating position is roughened evenly and finely, and the surface roughness reaches Ra: 2.0-2.5um; the UHTC high temperature corrosion resistant coating / spherical high purity alumina composite powder spraying thickness ratio is 1:10.5.

[0034] Step S5 plasma spraying: spray the high-purity alumina composite powder and UHTC high-temperature corrosion-resistant coating prepared in step S2 and step S3 at the hanging head position in sequence, use spray granulated spherical high-purity alumina powder as the coating material, the powder has high sphericity and good fluidity, the powder particle size distribution range is 15-45μm, the alumina purity is above 99.5%, use plasma spraying process, spraying current 600A, voltage 75V, main gas is argon, flow rate 45L / M, secondary gas is hydrogen, flow rate 7.5L / M, powder feeding rate 25g / min, coating thickness 0.1mm, that is, a thermal protective coating for optical fiber preform quartz handle fusion is obtained. Example 3

[0035] Step S1: Preparation of spherical high-purity alumina raw material: The spherical high-purity alumina is obtained by ultrasonication of aluminum powder in ultrapure water: Tetramethylammonium hydroxide is mixed with pure water, wherein the resistivity of the pure water is greater than 10 5 Ω·cm, and then aluminum powder is added, wherein the Al content of the aluminum powder is greater than 99.999%, and the above solution is reacted at 90°C and 40kHz ultrasonic frequency for 2h to obtain a slurry; the slurry is filtered, dried at 50°C and calcined at 1250°C to obtain the high-purity alumina powder.

[0036] Step S2 prepares spherical high-purity alumina composite powder: the high-purity alumina prepared in step S1 is mixed with a trace amount of graphene nanosheets to obtain the spherical high-purity alumina composite powder; the mass fraction of the graphene nanosheets is 0.2 parts, and the graphene nanosheets are composed of multiple stacked graphene layers, the graphene nanosheets are 7 layers, the total thickness is 2.0nm, and the graphene nanosheet size is 3.6μm; the mass fraction of high-purity alumina is 99.8 parts; the preparation process of the spherical high-purity alumina composite powder is as follows: the graphene nanosheets and high-purity spherical alumina powder are evenly mixed according to the ratio and ball-milled for 5h, the ball-milled mixed powder is dried at 70°C, and then a polyvinyl alcohol solution is added to granulate, and the mass ratio of the mixed powder of graphene nanosheets and high-purity spherical alumina to the polyvinyl alcohol solution is 3:1.

[0037] Step S3 Preparation of UHTC high temperature corrosion resistant coating raw material composition: The raw materials for preparing the UHTC high temperature corrosion resistant coating include alumina, inert powder, metal oxide and auxiliary powder; the preparation process of the UHTC high temperature corrosion resistant coating raw material composition is to mix the above-mentioned inert powder, metal oxide and auxiliary powder in proportion, and then put them into a ball mill in a dry state and then liquid phase sinter them, and the sintering temperature is 1350°C; the sintered powder is taken out and ball milled for a second time, and finally dried at 80°C to obtain the UHTC high temperature corrosion resistant coating raw material composition powder; wherein the mass fraction of the inert powder is 2.2 parts, the mass fraction of the metal oxide is 2.8 parts, the mass fraction of the auxiliary powder is 1.0 parts, and the rest is high-purity alumina powder; in the inert powder, the mass ratio of zirconium dioxide ZrO2 and mullite powder is 3:1; in the metal oxide, the mass ratio of calcium oxide, magnesium oxide and zinc oxide is 2:1:1.

[0038] Step S4: Pretreatment of the hanging head: A protective tape is attached to the end face of the quartz handle bar and other non-coated areas of the handle bar, and then the hanging head is sandblasted for roughening; 80#-120# white corundum sand is used for roughening, the sandblasting pressure is 0.25Mpa, the sandblasting angle is 75°, the coating position is roughened evenly and finely, and the surface roughness reaches Ra: 2.0-2.5um; the UHTC high temperature corrosion resistant coating / spherical high purity alumina composite powder spraying thickness ratio is 1:9.3.

[0039] Step S5 plasma spraying: spray the high-purity alumina composite powder and UHTC high-temperature corrosion-resistant coating prepared in step S2 and step S3 at the hanging head position in sequence, use spray granulated spherical high-purity alumina powder as the coating material, the powder has high sphericity and good fluidity, the powder particle size distribution range is 27-45μm, the alumina purity is above 99.5%, use plasma spraying process, spraying current 600A, voltage 75V, main gas is argon, flow rate 45L / M, secondary gas is hydrogen, flow rate 7.5L / M, powder feeding rate 25g / min, coating thickness 0.87mm, that is, a thermal protective coating for optical fiber preform quartz handle fusion is obtained. Example 4

[0040] Step S1: Preparation of spherical high-purity alumina raw material: The spherical high-purity alumina is obtained by ultrasonication of aluminum powder in ultrapure water: Tetramethylammonium hydroxide is mixed with pure water, wherein the resistivity of the pure water is greater than 10 5 Ω·cm, and then aluminum powder is added, wherein the Al content of the aluminum powder is greater than 99.999%, and the above solution is reacted at 80°C and 40kHz ultrasonic frequency for 2h to obtain a slurry; the slurry is filtered, dried at 60°C and calcined at 1300°C to obtain the high-purity alumina powder.

[0041] Step S2 prepares spherical high-purity alumina composite powder: the high-purity alumina prepared in step S1 is mixed with a trace amount of graphene nanosheets to obtain the spherical high-purity alumina composite powder; the mass fraction of the graphene nanosheets is 0.3 parts, and the graphene nanosheets are composed of multiple stacked graphene layers, the graphene nanosheets are 8 layers, the total thickness is 2.1nm, and the graphene nanosheet size is 4μm; the mass fraction of high-purity alumina is 99.7 parts; the preparation process of the spherical high-purity alumina composite powder is as follows: the graphene nanosheets and high-purity spherical alumina powder are evenly mixed according to the ratio and ball-milled for 4.5h, the ball-milled mixed powder is dried at 70°C, and then a polyvinyl alcohol solution is added for granulation, and the mass ratio of the mixed powder of graphene nanosheets and high-purity spherical alumina to the polyvinyl alcohol solution is 4:1.

[0042] Step S3 Preparation of UHTC high temperature corrosion resistant coating raw material composition: The raw materials for preparing the UHTC high temperature corrosion resistant coating include alumina, inert powder, metal oxide and auxiliary powder; the preparation process of the UHTC high temperature corrosion resistant coating raw material composition is to mix the above-mentioned inert powder, metal oxide and auxiliary powder in proportion, and then put them into a ball mill in a dry state and then liquid phase sinter them, and the sintering temperature is 1350°C; the sintered powder is taken out and ball milled for a second time, and finally dried at 90°C to obtain the UHTC high temperature corrosion resistant coating raw material composition powder; wherein the mass fraction of the inert powder is 3.5 parts, the mass fraction of the metal oxide is 1 part, the mass fraction of the auxiliary powder is 1 part, and the rest is high-purity alumina powder; in the inert powder, the mass ratio of zirconium dioxide ZrO2 and mullite powder is 3:1; in the metal oxide, the mass ratio of calcium oxide, magnesium oxide and zinc oxide is 1.5:1:1.

[0043] Step S4: Pretreatment of the hanging head: A protective tape is attached to the end face of the quartz handle bar and other non-coated areas of the handle bar, and then the hanging head is sandblasted for roughening; 80#-120# white corundum sand is used for roughening, the sandblasting pressure is 0.15-0.3Mpa, the sandblasting angle is 70°-80°, the coating position is roughened evenly and finely, and the surface roughness reaches Ra: 2.0-2.5um; the UHTC high temperature corrosion resistant coating / spherical high purity alumina composite powder spraying thickness ratio is 1:10.2.

[0044] Step S5 plasma spraying: spray the high-purity alumina composite powder and UHTC high-temperature corrosion-resistant coating prepared in step S2 and step S3 at the hanging head position in sequence, use spray granulated spherical high-purity alumina powder as the coating material, the powder has high sphericity and good fluidity, the powder particle size distribution range is 25-45μm, the alumina purity is above 99.5%, use plasma spraying process, spraying current 600A, voltage 75V, main gas is argon, flow rate 45L / M, secondary gas is hydrogen, flow rate 7.5L / M, powder feeding rate 25g / min, coating thickness 0.08mm, that is, a thermal protective coating for optical fiber preform quartz handle fusion is obtained. Example 5

[0045] Step S1: Preparation of spherical high-purity alumina raw material: The spherical high-purity alumina is obtained by ultrasonication of aluminum powder in ultrapure water: Tetramethylammonium hydroxide is mixed with pure water, wherein the resistivity of the pure water is greater than 10 5 Ω·cm, and then aluminum powder is added, wherein the Al content of the aluminum powder is greater than 99.999%, and the above solution is reacted at 85°C and 40kHz ultrasonic frequency for 2h to obtain a slurry; the slurry is filtered, dried at 55°C and calcined at 1250°C to obtain the high-purity alumina powder.

[0046] Step S2 prepares spherical high-purity alumina composite powder: the high-purity alumina prepared in step S1 is mixed with a trace amount of graphene nanosheets to obtain the spherical high-purity alumina composite powder; the mass fraction of the graphene nanosheets is 0.21 parts, and the graphene nanosheets are composed of multiple stacked graphene layers, the graphene nanosheets are 7 layers, the total thickness is 2.2nm, and the graphene nanosheet size is 4.2μm; the mass fraction of high-purity alumina is 99.85 parts; the preparation process of the spherical high-purity alumina composite powder is as follows: the graphene nanosheets and high-purity spherical alumina powder are evenly mixed according to the ratio and ball-milled for 6h, the ball-milled mixed powder is dried at 75°C, and then a polyvinyl alcohol solution is added for granulation, and the mass ratio of the mixed powder of graphene nanosheets and high-purity spherical alumina to the polyvinyl alcohol solution is 3.5:1.

[0047] Step S3 Preparation of UHTC high temperature corrosion resistant coating raw material composition: The raw materials for preparing the UHTC high temperature corrosion resistant coating include alumina, inert powder, metal oxide and auxiliary powder; the preparation process of the UHTC high temperature corrosion resistant coating raw material composition is to mix the above-mentioned inert powder, metal oxide and auxiliary powder in proportion, and then put them into a ball mill in a dry state and then liquid phase sinter them, and the sintering temperature is 1350°C; the sintered powder is taken out and ball milled for a second time, and finally dried at 80-100°C to obtain the UHTC high temperature corrosion resistant coating raw material composition powder; wherein the mass fraction of the inert powder is 3.8 parts, the mass fraction of the metal oxide is 1.5 parts, the mass fraction of the auxiliary powder is 1.2 parts, and the rest is high-purity alumina powder; in the inert powder, the mass ratio of zirconium dioxide ZrO2 and mullite powder is 3:1; in the metal oxide, the mass ratio of calcium oxide, magnesium oxide and zinc oxide is 1.6:1:1.

[0048] Step S4: Pretreatment of the hanging head: A protective tape is attached to the end face of the quartz handle bar and other non-coated areas of the handle bar, and then the hanging head is sandblasted for roughening; 80#-120# white corundum sand is used for roughening, the sandblasting pressure is 0.25Mpa, the sandblasting angle is 70°, the coating position is roughened evenly and finely, and the surface roughness reaches Ra: 2.0-2.5um; the UHTC high temperature corrosion resistant coating / spherical high purity alumina composite powder spraying thickness ratio is 1:9.9.

[0049] Step S5 plasma spraying: spray the high-purity alumina composite powder and UHTC high-temperature corrosion-resistant coating prepared in step S2 and step S3 at the hanging head position in sequence, use spray granulated spherical high-purity alumina powder as the coating material, the powder has high sphericity and good fluidity, the powder particle size distribution range is 30-45μm, the alumina purity is above 99.5%, use plasma spraying process, spraying current 600A, voltage 75V, main gas is argon, flow rate 45L / M, secondary gas is hydrogen, flow rate 7.5L / M, powder feeding rate 25g / min, coating thickness 0.1mm, that is, a thermal protective coating for optical fiber preform quartz handle fusion is obtained. Example 6

[0050] Step S1: Preparation of spherical high-purity alumina raw material: The spherical high-purity alumina is obtained by ultrasonication of aluminum powder in ultrapure water: Tetramethylammonium hydroxide is mixed with pure water, wherein the resistivity of the pure water is greater than 10 5 Ω·cm, and then aluminum powder is added, wherein the Al content of the aluminum powder is greater than 99.999%, and the above solution is reacted at 90°C and 40kHz ultrasonic frequency for 2h to obtain a slurry; the slurry is filtered, dried at 50°C and calcined at 1250°C to obtain the high-purity alumina powder.

[0051] Step S2 prepares spherical high-purity alumina composite powder: the high-purity alumina prepared in step S1 is mixed with a trace amount of graphene nanosheets to obtain the spherical high-purity alumina composite powder; the mass fraction of the graphene nanosheets is 0.2 parts, and the graphene nanosheets are composed of multiple stacked graphene layers, the graphene nanosheets are 7 layers, the total thickness is 2.0nm, and the graphene nanosheet size is 3.6μm; the mass fraction of high-purity alumina is 99.8 parts; the preparation process of the spherical high-purity alumina composite powder is as follows: the graphene nanosheets and high-purity spherical alumina powder are evenly mixed according to the ratio and ball-milled for 5h, the ball-milled mixed powder is dried at 70°C, and then a polyvinyl alcohol solution is added to granulate, and the mass ratio of the mixed powder of graphene nanosheets and high-purity spherical alumina to the polyvinyl alcohol solution is 3:1.

[0052] Step S3: Pretreatment of the hanging head: Affix protective tape to the end face of the quartz handle bar and other non-coated areas of the handle bar, and then sandblast the hanging head for roughening; sandblasting uses 80#-120# white corundum sand, the sandblasting pressure is 0.25Mpa, the sandblasting angle is 75°, the coating position is roughened evenly and finely, and the surface roughness reaches Ra: 2.0-2.5um.

[0053] Step S4 plasma spraying: spray the high-purity alumina composite powder coating prepared in step S2 at the hanging head position, using spray granulated spherical high-purity alumina powder as the coating material, the powder has high sphericity and good fluidity, the powder particle size distribution range is 27-45μm, the alumina purity is above 99.5%, and a plasma spraying process is used. The spraying current is 600A, the voltage is 75V, the main gas is argon, the flow rate is 45L / M, the secondary gas is hydrogen, the flow rate is 7.5L / M, the powder feeding rate is 25g / min, and the coating thickness is 0.87mm, so as to obtain a thermal protective coating for optical fiber preform quartz handle welding. Example 7

[0054] Step S1 Preparation of UHTC high temperature corrosion resistant coating raw material composition: The raw materials for preparing the UHTC high temperature corrosion resistant coating include alumina, inert powder, metal oxide and auxiliary powder; the preparation process of the UHTC high temperature corrosion resistant coating raw material composition is to mix the above-mentioned inert powder, metal oxide and auxiliary powder in proportion, and then put them into a ball mill in a dry state and then liquid phase sinter them, and the sintering temperature is 1350°C; the sintered powder is taken out and ball milled for a second time, and finally dried at 80°C to obtain the UHTC high temperature corrosion resistant coating raw material composition powder; wherein the mass fraction of the inert powder is 2.2 parts, the mass fraction of the metal oxide is 2.8 parts, the mass fraction of the auxiliary powder is 1.0 parts, and the rest is high-purity alumina powder; in the inert powder, the mass ratio of zirconium dioxide ZrO2 and mullite powder is 3:1; in the metal oxide, the mass ratio of calcium oxide, magnesium oxide and zinc oxide is 2:1:1.

[0055] Step S2: Pretreatment of the hanging head: A protective tape is attached to the end face of the quartz handle bar and other non-coated areas of the handle bar, and then the hanging head is sandblasted for roughening; 80#-120# white corundum sand is used for roughening, the sandblasting pressure is 0.25Mpa, the sandblasting angle is 75°, the coating position is roughened evenly and finely, and the surface roughness reaches Ra: 2.0-2.5um.

[0056] Step S3 plasma spraying: spray the UHTC high temperature corrosion resistant coating prepared in step S1 at the hanging head position, use spray granulated spherical high purity alumina powder as the coating material, the powder has high sphericity and good fluidity, the powder particle size distribution range is 27-45μm, the alumina purity is above 99.5%, use plasma spraying process, spraying current 600A, voltage 75V, main gas is argon, flow rate 45L / M, secondary gas is hydrogen, flow rate 7.5L / M, powder feeding rate 25g / min, coating thickness is 0.87mm, and a thermal protective coating for optical fiber preform quartz handle fusion is obtained. Comparative Example 1

[0057] Different from the embodiment, the thermal protection coating of this comparative example adopts a single high-purity aluminum oxide powder coating. Comparative Example 2

[0058] Different from the embodiment, the comparative example does not use a heat protection coating on the optical fiber preform fused quartz handle rod.

[0059] In the above-mentioned embodiments and comparative examples, the porosity and microhardness of the alumina protective coating at the hanging head position were detected, and the deformation degree of the quartz handle hanging rod head during the welding process was observed.

[0060] The coating porosity is calculated as follows:

[0061] in: P is the coating porosity, unit is %; V0 is the volume of the paint in its natural state, in cm 3 ; V is the absolute dense volume of the coating, in cm 3 .

[0062] Microhardness 1HV = constant × test force / indentation surface area = 0.102 × 2Fsin (136° / 2) / d 2 ≈0.1891·F / d 2 ; The coating porosity and microhardness test results are shown in Table 1: Table 1 Porosity and microhardness of coatings

[0063] The deformation degree detection process of the quartz handle rod hanging rod head is to place the coated quartz handle rod at a high temperature spray gun at 1200℃, 1400℃, 1500℃, and 1800℃ for spraying for 3 minutes. The test results are shown in Table 2 below: Table 2 Observation results of deformation degree

[0064] It can be seen from the above test result table that the porosity, microhardness and thermal deformation resistance of the welded thermal protective coating prepared by the experimental condition parameter ratio of Example 3 are the best. The coating porosity is only 3.54%, and its microhardness reaches the HV996 level. In addition, Examples 1-5 all underwent thermal deformation when sprayed with a high temperature gun at 1800°C for 2 minutes.

[0065] In Example 6, only a single spherical high-purity alumina coating was sprayed, and its porosity was 7.28%, the microhardness reached HV813, and slight thermal deformation occurred at 1800°C. It can be seen that its comprehensive performance is slightly inferior to that of Examples 1-5; it can be seen that only spraying a single spherical high-purity alumina coating cannot achieve the same excellent technical effect as the solution of the present invention; In Example 7, only a single UHTC high temperature corrosion resistant coating was sprayed, and its porosity was 7.82%, and its microhardness was HV766, which was slightly inferior to that of Example 6. Its thermal deformation test was the same as that of Example 6, and there was slight deformation at 1800°C.

[0066] Compared with Comparative Example 1, high-purity alumina and graphene nanosheets were not used in combination, and UHTC coating was not added. Its porosity, microhardness and thermal deformation resistance were poor, so it was not evaluated.

Claims

1. A thermal protection coating for welding a quartz handle of an optical fiber preform rod, characterized in that: The fusion-bonded thermal protective coating comprises the following preparation steps: Step S1: Preparation of spherical high-purity alumina raw material: The spherical high-purity alumina is obtained by ultrasonicating aluminum powder in ultrapure water; Step S2: preparing spherical high-purity alumina composite powder: mixing the high-purity alumina prepared in step S1 with a trace amount of graphene nanosheets to prepare the spherical high-purity alumina composite powder; Step S3: Preparation of raw material composition of UHTC high temperature corrosion resistant coating: the raw materials for preparing the UHTC high temperature corrosion resistant coating include aluminum oxide, inert powder, metal oxide and auxiliary powder; Step S4: Pre-treatment of the hanging head: Affix protective tape to the end surface of the quartz handle bar and other non-coated areas of the handle bar, and then sandblast the hanging head for roughening; Step S5 plasma spraying: spray the high-purity alumina composite powder and UHTC high-temperature corrosion-resistant coating prepared in step S2 and step S3 at the hanging head position in sequence, so as to obtain a thermal protection coating for the fusion welding of the optical fiber preform quartz handle.

2. The optical fiber preform quartz handle welding thermal protection coating according to claim 1, characterized in that: The raw materials for preparing the spherical high-purity alumina raw material in step S1 also include tetramethylammonium hydroxide, and the preparation process is: mixing tetramethylammonium hydroxide with pure water, wherein the resistivity of the pure water is greater than 10 5 Ω·cm, and then aluminum powder is added, wherein the Al content of the aluminum powder is greater than 99.999%, and the above solution is reacted at 80-90°C and 35-45kHz ultrasonic frequency for 2h to obtain a slurry; the slurry is filtered, dried at 40-60°C and calcined at 1200-1300°C to obtain the high-purity alumina powder.

3. The optical fiber preform quartz handle welding thermal protection coating according to claim 1, characterized in that: The mass fraction of the graphene nanosheets in step S2 is 0.1-0.5 parts; the mass fraction of high-purity alumina is 99.5-99.9 parts; the preparation process of the spherical high-purity alumina composite powder is as follows: the graphene nanosheets and high-purity spherical alumina powder are mixed evenly according to the ratio and ball-milled for 3-8 hours, the ball-milled mixed powder is dried at 50-80°C, and then a polyvinyl alcohol solution is added for granulation, and the mass ratio of the mixed powder of graphene nanosheets and high-purity spherical alumina to the polyvinyl alcohol solution is (1-5):

1.

4. The optical fiber preform quartz handle welding thermal protection coating according to claim 3, characterized in that: The graphene nanosheet is composed of a plurality of stacked graphene layers. The graphene nanosheet has 6 to 8 layers, a total thickness of 1.8 to 2.5 nm, and a size of 3 to 5 μm.

5. The optical fiber preform quartz handle welding thermal protection coating according to claim 1, characterized in that: In step S3, the inert powder is zirconium dioxide ZrO2 and mullite powder; the metal oxide is a combination of calcium oxide, magnesium oxide and zinc oxide; and the auxiliary agent powder is silicon dioxide and boron trioxide.

6. The optical fiber preform quartz handle welding thermal protection coating according to claim 5, characterized in that: The preparation process of the UHTC high-temperature corrosion-resistant coating raw material composition is as follows: the above-mentioned inert powder, metal oxide and auxiliary powder are mixed evenly in proportion, and then put into a ball mill in a dry state and liquid-phase sintered, and the sintering temperature is 1300-1400°C; the sintered powder is taken out and ball-milled for a second time, and finally dried at 80-100°C to obtain the UHTC high-temperature corrosion-resistant coating raw material composition powder; wherein the mass fraction of the inert powder is 1-5 parts, the mass fraction of the metal oxide is 1-5 parts, the mass fraction of the auxiliary powder is 0.5-2 parts, and the rest is high-purity alumina powder; in the inert powder, the mass ratio of zirconium dioxide ZrO2 and mullite powder is 3:1; in the metal oxide, the mass ratio of calcium oxide, magnesium oxide and zinc oxide is (1-2):1:

1.

7. The optical fiber preform quartz handle welding thermal protection coating according to claim 1, characterized in that: In the step S4 of hanging head pretreatment, 80#-120# white corundum sand is used for sandblasting, the sandblasting pressure is 0.15-0.3Mpa, the sandblasting angle is 70°-80°, the coating position is coarsened uniformly and finely, and the surface roughness reaches Ra: 2.0-2.5um.

8. The optical fiber preform quartz handle welding thermal protection coating according to claim 1, characterized in that: In the plasma spraying of step S5, the UHTC high temperature corrosion resistant coating is sprayed first, and then the spherical high purity alumina composite powder is sprayed, and the spraying thickness ratio of the UHTC high temperature corrosion resistant coating / spherical high purity alumina composite powder is 1:(8.8-10.5).

9. The optical fiber preform quartz handle welding thermal protection coating according to claim 8, characterized in that: Spray granulated spherical high-purity alumina powder is used as the coating material. The powder has high sphericity and good fluidity. The powder particle size distribution range is 15-45μm, and the purity of alumina is above 99.5%. The plasma spraying process is used, the spraying current is 600A, the voltage is 75V, the main gas is argon, the flow rate is 45L / M, the secondary gas is hydrogen, the flow rate is 7.5L / M, the powder feeding rate is 25g / min, and the coating thickness is 0.05-0.1mm.

10. An application of a thermal protection coating for welding a quartz handle of an optical fiber preform rod, characterized in that: It can be used in the process of fusing the optical fiber preform rod to the quartz handle rod. The porosity of the alumina protective coating at the hanging head position is 4-6%, and the microhardness reaches HV800-1000. The coating has high strength and high temperature resistance, protects the quartz substrate from deformation, and has an effective and stable working state.